Conceptualizing knowledge transfer between expatriates and host country nationals: the mediating effect of social capital - Ismail, Maimunah (Cogent OA, 2015)
This paper aims to propose a conceptual model of knowledge transfer by relating two specific personal factors of expatriate and host country national (HCN) dyads as antecedents of knowledge transfer, and mediated by social capital factors. An intensive literature review method was employed to identify and analyse relevant literatures. The paper used a dyadic bi-directional approach in theorizing knowledge transfer by integrating the social capital theory, and the anxiety and uncertainty management theory. The paper considers two personal factors (cultural intelligence and knowledge-seeking behaviour) and two social capital variables (trust and shared vision) as mediators of knowledge transfer. Upon model validation, the paper could offer practical interventions for human resource practitioners and managers to assist multinational corporations towards managing knowledge transfer involving expatriates and HCNs.